The Role of the BAKUNG Village Library in Fostering a Culture of Community Literacy in Sidoarjo Regency: Peran Perpustakaan Desa BAKUNG dalam Menumbuhkan Budaya Literasi Masyarakat di Kabupaten Sidoarjo - Rohma, Zazilah; Agustin, Isna Fitria (Indonesian Journal of Public Policy Review, 2022)
The rapid development of technology and science makes information important for people in everyday life. To cultivate an interest in reading, people need special attention from various parties, namely schools, parents, government and libraries. Libraries become a bridge that connects information sources with their readers, so that their existence is very important, namely as a means of learning media resources. The purpose of this study is to describe and analyze the implementation of the village library’s role in fostering a literacy culture to increase people’s reading interest and to analyze and describe the supporting and inhibiting factors of the village library’s role in fostering a literacy culture to increase people’s reading interest. This research is a qualitative research, using case study method. The subjects in this study were the village head, the community, and the Rejeni village librarian. Data collection techniques used in this study were observation, interviews and documentation. Meanwhile, the data analysis and interpretation techniques carried out were in accordance with those proposed by Miles and Huberman, namely data reduction, data presentation and data verification. The results of this study indicate that the library has a very large role in increasing people’s reading interest in fostering a literacy culture. However, in order to achieve the desired goal, the steps that must be carried out are to provide complete book collections, complementing existing facilities and infrastructure, so as to be able to create a comfortable library atmosphere and excellent and superior library services. While the influencing factors are service hours during the pandemic, lack of facilities related to IT, good cooperation between employees, and incomplete book collections.